2021
DOI: 10.9734/jpri/2021/v33i60b35007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Correlation of Preoperative Serum C- Reactive Protein, Neutrophil-lymphocyte Ratio and Platelet-lymphocyte Ratio for Cervical Metastasis in Patients of Primary Oral Squamous Cell Carcinoma

Abstract: Background: The influence of cervical metastasis on prognosis in a person who is suffering from oral squamous cell carcinoma (OSCC) has been notorious. C- reactive protein (CRP) is a prior biomarker for inflammation. Recent literature provide evidence of systemic inflammatory markers playing important role in determining survival rate on patient with OSCC. Hence, in current study the “utility of Neutrophil-lymphocyte ratio (NLR) ,Platelet-lymphocyte ratio (PLR), and serum CRP are evaluated and correlated for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Among the etiologies of malignant neoplasia, chronic inflammation has been identified as the main cause of about 20% of malignant neoplasia cases [32].Although CRP is an egg self that reflects the acute response of the body, it has been shown that CRP levels also reflect the body's early defense system [33]. The potential predictive value of CRP in OSCC lymph node metastasis has been demonstrated in a prospective study of 40 OSCC patients [34]. This calls for a large number of prospective studies to further understand the potential value of CRP in assessing OSCC progression as well as the mechanisms.…”
Section: Peripheral Blood Immunoinflammatory Markers In Oral Squamous...mentioning
confidence: 99%
“…Among the etiologies of malignant neoplasia, chronic inflammation has been identified as the main cause of about 20% of malignant neoplasia cases [32].Although CRP is an egg self that reflects the acute response of the body, it has been shown that CRP levels also reflect the body's early defense system [33]. The potential predictive value of CRP in OSCC lymph node metastasis has been demonstrated in a prospective study of 40 OSCC patients [34]. This calls for a large number of prospective studies to further understand the potential value of CRP in assessing OSCC progression as well as the mechanisms.…”
Section: Peripheral Blood Immunoinflammatory Markers In Oral Squamous...mentioning
confidence: 99%